(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
In this paper we consider the family of operator matrices H (K) of order three which depends on the parameter K. This family of operator matrices are act in the three-particle cut subspace of the bosonic Fock space. We constract the Weinberg equation for the eigenvectors of H (K).